Quizizz: Basic accounting equation learning at SMK Negeri 11 Bandung - Fauzan Akbar Rahman Putra; Tazkia Khoirunnisa Buana (Curricula: Journal of Curriculum Development, 2024)
This study investigates how the Quizizz platform teaches the basic concept of accounting equations in Vocational High Schools. The accounting equation is a fundamental concept in learning accounting. A good understanding of this concept is needed because it is fundamental to learning and will be very useful for vocational high school students entering the world of work. However, there are still many vocational students who do not have a good understanding of this concept. Therefore, a study was conducted using a descriptive quantitative method involving 20 students at SMK Negeri 11 Bandung. Data was collected through observation and questionnaires. The results showed that using Quizizz significantly improved students' understanding of the basic concepts of accounting equations. Students who use Quizizz have a higher average score on the test of understanding the basic concepts of accounting equations than those who do not use Quizizz. In addition, students enjoyed learning accounting more and understood the subject better using Quizizz.